2022
DOI: 10.1002/cyto.b.22088
|View full text |Cite
|
Sign up to set email alerts
|

B‐lineage antigens that are useful to substitute CD19 for minimal residual disease monitoring in B cell precursor acute lymphoblastic leukemia after CD19 targeting

Abstract: Background: The potential loss of CD19 during targeted treatment of B cell precursor acute lymphoblastic leukemia (BCP-ALL) can hamper flow cytometric minimal residual disease (MRD) monitoring. In the current study, we present expression data for antigens that are candidates for CD19 substitution: surface CD22, CD24, CD10, and intracellular (i) CD79a.Methods: Bone marrow samples from 519 consecutive children (below 18 y.o.) with primary BCP-ALL were studied with a focus on expression of CD19, CD10, CD22, CD24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…Because of the high incidence of CD19 negativity, it was necessary to search for a possible substitution for CD19 as the primary B-lineage antigen with antigen(s) of similar diagnostic value. The initial expression of CD22, CD24, CD10 and intracellular (i) CD79a was tested in a large cohort of primary BCP-ALL pediatric patients ( n = 519) [ 20 ]. It was found that the tested antigens were expressed by nearly all tumor cells (more than 95% of positive cells in the leukemic population) in 88.9% (CD22), 83.7% (iCD79a), 88.2% (CD10) and 94.7% (CD24) of patients [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high incidence of CD19 negativity, it was necessary to search for a possible substitution for CD19 as the primary B-lineage antigen with antigen(s) of similar diagnostic value. The initial expression of CD22, CD24, CD10 and intracellular (i) CD79a was tested in a large cohort of primary BCP-ALL pediatric patients ( n = 519) [ 20 ]. It was found that the tested antigens were expressed by nearly all tumor cells (more than 95% of positive cells in the leukemic population) in 88.9% (CD22), 83.7% (iCD79a), 88.2% (CD10) and 94.7% (CD24) of patients [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The initial expression of CD22, CD24, CD10 and intracellular (i) CD79a was tested in a large cohort of primary BCP-ALL pediatric patients ( n = 519) [ 20 ]. It was found that the tested antigens were expressed by nearly all tumor cells (more than 95% of positive cells in the leukemic population) in 88.9% (CD22), 83.7% (iCD79a), 88.2% (CD10) and 94.7% (CD24) of patients [ 20 ]. Moreover, at least one of the studied markers was expressed on nearly all blasts in more than 95% of patients, and there were no patients in whom none of these antigens were found.…”
Section: Methodsmentioning
confidence: 99%
“…Мониторинг минимальной остаточной болезни (МОБ) проводился методом многоцветной проточной цитометрии согласно стандарту группы «Москва-Берлин» [5] с модификациями, необходимыми для эффективного определения МОБ в условиях проведения CD19-направленной терапии [6,7]. Кинетика МОБ на всем протяжении терапии показана на рисунке 5.…”
Section: клеточная терапияunclassified
“…Similarly upon daratumumab treatment the identification of malignant plasma cells is not feasible with anti-CD38 labeling. In this Issue of Clinical Cytometry (Mikhailova et al, 2022) Mikhailova and coworkers investigated the applicable B-lineage markers in case of minimal residual disease detection in children suffering from B-cell precursor acute lymphoblastic leukemia after CD19 targeting. The pan B-cell surface marker CD19 molecule can be targeted either with the bispecific antibody blinatumomab or with T-lymphocytes harboring a chimeric antigen receptor against CD19.…”
Section: When Lineage Assignment Becomes a Challengementioning
confidence: 99%